The impact of private sector credit on income inequalities in European Union (15 member states) - Ionuț Jianu (Theoretical and Applied Economics, 2017)
This paper aims to provide a comprehensive analysis on the income inequalities recorded in the EU-15 in the 1995-2014 period and to estimate the impact of private sector credit on income disparities. In order to estimate the impact, I used the panel data technique with 15 cross-sections for the first 15 Member States of the European Union, applying generalized error correction model.
Keywords: C33; D63; E51; 330; credit; error correction model; European Union; income inequality; panel